Pemberdayaan Masyarakat Ubah Limbah menjadi Berkah : Pemanfaatan Minyak Jelantah sebagai Bahan Dasar Sabun Cair di Desa Jawisari - Iysfa Imroatun Adilla; Aulia Muthiatus Sa’adah; Chandra Wijaya; Diyah Pitaloka; Icah Hamidah; Kamila Rosyada; Mela Purnamasari; Melysa Septiana; Lenni Khotimah Harahap (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
The Workshop program for training in making soap from used cooking oil is one of the work programs of the Regular Community Service Program (KKN) 83 UIN Walisongo Semarang Post 16 which was carried out with the mothers of Jawisari Village at the Jawisari Village Hall, Limbangan District, Kendal Regency. This workshop program was motivated by the fact that many people still use used cooking oil repeatedly so that it can endanger their health and there are still those who dispose of used cooking oil carelessly so that it can cause environmental pollution. This work program aims to provide an understanding to the community about the negative impacts of used cooking oil waste on the environment and health, introduce the application of science and technology through training in processing used cooking oil waste, and provide training and assistance to control environmental pollution by providing education and training to local residents on how to process used cooking oil waste into liquid soap. This training workshop activity was carried out in three main stages, namely counseling, practicing making liquid soap, and evaluation. The results of this program show that the training workshop activities were successful and well-run where participants were able to understand the basic techniques of making liquid soap and gain direct experience in practice, the mothers who participated were also very enthusiastic and actively participated and felt happy to be able to learn to change used cooking oil waste into liquid soap products that are useful for everyday life. Making liquid soap from used cooking oil is an innovation that is not only useful for reducing waste oil that pollutes the environment, but also provides economic and social benefits for the community because it can open up business opportunities and support the local economy. Therefore, as a sustainable step, it is necessary to provide education to the community about the importance of recycling used cooking oil and improving technology in the production of liquid soap to be more efficient and environmentally friendly